2019
DOI: 10.1242/jcs.222059
|View full text |Cite
|
Sign up to set email alerts
|

Tau modulates Schwann cell proliferation, migration and differentiation following peripheral nerve injury

Abstract: Tau protein (encoded by the gene microtubule-associated protein tau, Mapt) is essential for the assembly and stability of microtubule and the functional maintenance of the nervous system. Tau is highly abundant in neurons and is detectable in astrocytes and oligodendrocytes. However, whether tau is present in Schwann cells, the unique glial cells in the peripheral nervous system, is unclear. Here, we investigated the presence of tau and its coding mRNA, Mapt, in cultured Schwann cells and find that tau is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Studies exploring the role of tau after injury have also been contradictory. MAPT −/− mice suffer worse functional outcome after sciatic nerve injury [285] and EAE [277], reminiscent of tau regulating physiological myelination (discussed earlier). Several studies, however, report that MAPT −/− mice are resistant to some functional and cognitive deficits after TBI, although this depends on whether the injury was repetitive [45] and whether short-term or long-term outcomes were measured [256].…”
Section: The Effect Of Tau Depends On the Type Of Injury Inducedmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies exploring the role of tau after injury have also been contradictory. MAPT −/− mice suffer worse functional outcome after sciatic nerve injury [285] and EAE [277], reminiscent of tau regulating physiological myelination (discussed earlier). Several studies, however, report that MAPT −/− mice are resistant to some functional and cognitive deficits after TBI, although this depends on whether the injury was repetitive [45] and whether short-term or long-term outcomes were measured [256].…”
Section: The Effect Of Tau Depends On the Type Of Injury Inducedmentioning
confidence: 94%
“…MAPT −/− mice also show age-dependent degeneration of myelinated fibers, reduced nerve conduction, and progressive hypomyelination [157,237], resulting in motor [157] and nociceptive [237] impairments. Tau knockdown also restricts recovery after sciatic nerve damage, with mice showing defective myelin debris clearance and severely impaired Schwann cell migration and differentiation [285]. Similarly, MAPT −/− mice showed a worse clinical outcome after experimental autoimmune encephalomyelitis (EAE) (a model of demyelinating disease) [277].…”
Section: Tau Is Important For Normal Myelinationmentioning
confidence: 99%
“…Tau is a ubiquitous protein that is primarily expressed in the nervous system [ 7 ], with higher expression levels in neurons than astrocytes, oligodendrocytes, and Schwann cells [ 8 , 9 , 10 ]. In the brain tau, isoform expression is developmentally regulated: in fetal brain is expressed only the shortest isoform 0N3R [ 11 ], whereas the adult human brain shows all the isoforms [ 4 ].…”
Section: The Role Of Tau In Physiological Condition In Axonsmentioning
confidence: 99%
“…Schwann cells provide mechanical and trophic support to peripheral axons and are essential for the maintenance of peripheral nerves’ physiological function. It has been reported that tau is expressed in Schwann cells and is involved in Schwann cells’ mobility and phagocytosis ability; indeed, Yi and colleagues demonstrate that in MAPT -knockout mice, the decrease of tau expression reduced Schwann cell migration and suppressed the ability to clear debris after sciatic nerve injury [ 10 ]. Thus, tau pathology can induce neurotoxicity affecting not only neurons, but also damaging Schwann cells and preventing their trophic and supportive role.…”
Section: Pathological Tau and The Peripheral Nervous Systemmentioning
confidence: 99%
“…Primary Schwann cells were collected and cultured as previously described [15]. Brie y, cells isolated from neonatal SD rat sciatic nerves were puri ed with anti-Thy1.1 antibody (Sigma, St. Louis, MO, USA) and rabbit complement (Invitrogen, Carlsbad, CA, USA) and then cultured in DMEM (Gibco, Grand Island, NY, USA) containing 10% FBS (Gibco), 1% penicillin and streptomycin (Invitrogen), 2 μM forskolin (Sigma), and 10 ng/ml HRG (R&D Systems Inc., Minneapolis, MN, USA).…”
Section: Schwann Cell Culture and Treatmentmentioning
confidence: 99%